2023
DOI: 10.1111/dar.13640
|View full text |Cite
|
Sign up to set email alerts
|

Rolling through TikTok: An analysis of 3,4‐methylenedioxymethamphetamine‐related content

Abstract: IntroductionTikTok has quickly gained popularity through its platforming of large amounts of short video content. Given its widespread popularity, unrestricted access and poor content monitoring may allow 3,4‐methylenedioxymethamphetamine (MDMA)‐related content to influence perception of MDMA use. We aimed to investigate how MDMA‐related videos are portrayed on TikTok and explore MDMA‐related harm reduction content.MethodsMDMA‐related hashtags and sounds were utilised to collect data from TikTok (n = 498). Vid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Interestingly, both Whelan et al [6] and Mathieson et al [7] demonstrate that this tendency for substance use posts to be positive may not extend to all substances. Whelan et al found that the plurality of MDMA-related TikTok videos were neutral (40.6%), but posts were still more likely to be positive (34.9%) than negative (17.9%) [6].…”
Section: What Do People See?mentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, both Whelan et al [6] and Mathieson et al [7] demonstrate that this tendency for substance use posts to be positive may not extend to all substances. Whelan et al found that the plurality of MDMA-related TikTok videos were neutral (40.6%), but posts were still more likely to be positive (34.9%) than negative (17.9%) [6].…”
Section: What Do People See?mentioning
confidence: 99%
“…Interestingly, both Whelan et al [6] and Mathieson et al [7] demonstrate that this tendency for substance use posts to be positive may not extend to all substances. Whelan et al found that the plurality of MDMA-related TikTok videos were neutral (40.6%), but posts were still more likely to be positive (34.9%) than negative (17.9%) [6]. Likewise, Mathieson et al report that gabapentinoid-related tweets tend to be neutral (48.4% gabapentin/68.2% pregabalin), but that negative tweets (30.0% gabapentin/22.7% pregabalin) are more common than positive tweets (21.6% gabapentin/9.1% pregabalin) [7].…”
Section: What Do People See?mentioning
confidence: 99%
See 1 more Smart Citation